Introducing Information Security Readiness Evaluation Using the KAMI 5.0 Index Among Civil Servants in Purbalingga - Sarah Astiti; Sukmadiningtyas Sukmadiningtyas; Sevia Indah Purnama (Sarana Ilmu Indonesia (salnesia), 2026)
The escalation of cyber threats and the growing complexity of digital asset management within government agencies necessitate the strengthening of structured information security governance. This paper documents a community service initiative conducted at DINKOMINFO Purbalingga, aimed at enhancing human resource capabilities in implementing an Information Security Management System (ISMS). The primary focus of the program was the dissemination and simulation of the KAMI 5.0 Index instrument, which serves as the latest adaptation of the ISO/IEC 27001:2022 standard. The implementation method consisted of face-to-face training involving 23 participants from various cross-sectoral agencies, employing a theoretical-analytical approach. Evaluation results indicated an improvement in participants' comprehension regarding information asset classification and self-evaluation mechanisms. The majority of participants expressed a very high level of satisfaction (Strongly Agree) regarding the relevance of the material, although response variations reflected the dynamic nature of participants' understanding. The success of this initiative demonstrates DINKOMINFO's strategic readiness to transition towards a more rigorous and accountable national information security framework